2011
DOI: 10.1016/j.physletb.2011.04.037
|View full text |Cite
|
Sign up to set email alerts
|

Tensor perturbations of f(R)-branes

Abstract: We analyze the tensor perturbations of flat thick domain wall branes in f (R) gravity. Our results indicate that under the transverse and traceless gauge, the metric perturbations decouple from the perturbation of the scalar field. Besides, the perturbed equation reduces to the familiar Klein-Gordon equation for massless spin-2 particles only when the bulk curvature is a constant or when f (R) = R. As an application of our results, we consider the possibility of localizing gravity on some flat thick branes. Th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
29
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 58 publications
(31 citation statements)
references
References 58 publications
1
29
0
Order By: Relevance
“…However, the stability of f (T ) brane system is still unknown. In this paper we will focus on this issue and analyse the localization of the graviton zero mode, which is an important issue in brane model since it will ensure the four-dimensional Newtonian potential on the brane [28,[53][54][55][56][57][58][59][60][61][62][63][64][65][66][67]. This paper is organised as follows.…”
Section: Introductionmentioning
confidence: 99%
“…However, the stability of f (T ) brane system is still unknown. In this paper we will focus on this issue and analyse the localization of the graviton zero mode, which is an important issue in brane model since it will ensure the four-dimensional Newtonian potential on the brane [28,[53][54][55][56][57][58][59][60][61][62][63][64][65][66][67]. This paper is organised as follows.…”
Section: Introductionmentioning
confidence: 99%
“…For example, in f (R) gravity (see [19][20][21] for comprehensive reviews on f (R) gravity and its applications in cosmology), the effective potential is determined by both the warp factor and the form of f (R) (see Ref. [22] for details). So, in principle, graviton resonances can be turned on by tuning gravity.…”
Section: Introductionmentioning
confidence: 99%
“…However, in Ref. [22], the authors found that the tensor perturbation equation can be finally rewritten as a second order Schrödinger-like equation. The results of Ref.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the case of f (R) theories, the only investigation was presented in [15], where authors considered a flat thick domain wall branes supplemented with f (R) gravity. Nonetheless the full calculation of tensor perturbations for f (R) theories in metric formalism has never been presented before.…”
Section: Introductionmentioning
confidence: 99%